The Caring Continuum Evolved Hormonal and Proximal Mechanisms Explain Prosocial and Antisocial Extremes [article]. - Marsh, Abigail A.
Implicit in the long-standing disagreements about whether humans? fundamental nature is predominantly caring or callous is an assumption of uniformity. This article reviews evidence that instead supports inherent variation in caring motivation and behavior. The continuum between prosocial and antisocial extremes reflects variation in the structure and function of neurohormonal systems originally adapted to motivate parental care and since repurposed to support generalized forms of care. Extreme social behaviors such as extraordinary acts of altruism and aggression can often be best understood as reflecting variation in the neural systems that support care. A review of comparative, developmental, and neurobiological research finds consistent evidence that variations in caring motivations and behavior reflect individual differences in sensitivity to cues that signal vulnerability and distress and in the tendency to generalize care outward from socially close to distant others. The often complex relationships between caring motivation and various forms of altruism and aggression are discussed. -- (from the author)